2009
DOI: 10.1007/s10439-009-9865-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Motion and Loading System for a Rat Knee Joint In Vivo

Abstract: The influence of biomechanical stimuli on modulating cartilage homeostasis is well recognized. However, many aspects of cellular mechanotransduction in cartilage remain unknown. We developed a computer-controlled joint motion and loading system (JMLS) to study the biological response of cartilage under well-characterized mechanical loading environments. The JMLS was capable of controlling i) angular displacement, ii) motion frequency, iii) magnitude of the axial compressive load applied to the moving joint, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…There are other forms of mechanical loading such as joint rotation [26, 27], and whole-body and local vibrations [28, 29]. To our knowledge, however, no loading modality has been clinically applied for treatment of a femur neck or head.…”
Section: Discussionmentioning
confidence: 99%
“…There are other forms of mechanical loading such as joint rotation [26, 27], and whole-body and local vibrations [28, 29]. To our knowledge, however, no loading modality has been clinically applied for treatment of a femur neck or head.…”
Section: Discussionmentioning
confidence: 99%
“…During the middle of each immobilization period (for 6 and 24 hour groups), and daily, 12 hours after the initial application of the casts (for 7 day group), rats were anesthetized, the casts were removed, and the rats were placed on a joint loading system (Gu, et al 2009) for 1 hour. During that period, these rats were subjected to motion loading at a frequency of two cycles per minute, with a range of motion between 65° and 115°, while a separate group of rats were maintained in the device without motion, at 115° of knee flexion (sham group).…”
Section: Methodsmentioning
confidence: 99%
“…Gu et al (18) have shown that physical exercise can reduce pain, maintain a range of motion, and thus reduce the time of hospitalization or rehabilitation. Among physical exercises, those that are performed in water, which has the added benefits of the physical properties of water such as heat and pressure, can contribute to pain relief and the reduction of edema and can facilitate ease of movement (19).…”
Section: Introductionmentioning
confidence: 99%